2021
DOI: 10.17569/tojqi.767378
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous Online Learning Experiences of Students in Pandemic Process: Facilities, Challenges, Suggestions

Abstract: This study examined students' experiences in an asynchronous online learning environment. Students evaluated the asynchronous online learning environment in terms of interaction, feedback, academic and technical support, active learning and assessment. The study, which was carried out with a qualitative research approach, was conducted with 28 students studying in faculty of education. During the pandemic, students continued all their courses for 9 weeks with asynchronous distance education.At the end of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…According to the studies, students stated that distance education saves time and is economical, provides easy access to information and also to materials and lessons (M. F. Genç Genç et al, 2020;Ünal et al, 2021). In addition, studies revealed that students' independent learning skills were developed in the distance education process (Öztürk, 2021;Pasyk et al, 2021). Kör et al (2013) also found that the use of interactive materials such as animation, video and simulation in distance education lessons had a positive effect on success.…”
Section: Discussionmentioning
confidence: 99%
“…According to the studies, students stated that distance education saves time and is economical, provides easy access to information and also to materials and lessons (M. F. Genç Genç et al, 2020;Ünal et al, 2021). In addition, studies revealed that students' independent learning skills were developed in the distance education process (Öztürk, 2021;Pasyk et al, 2021). Kör et al (2013) also found that the use of interactive materials such as animation, video and simulation in distance education lessons had a positive effect on success.…”
Section: Discussionmentioning
confidence: 99%
“…"Sometimes there were several lecturers who gave assignments but the way the assignments were collected was difficult to understand and requires us to used several applications" (R.4). "Sometimes there were applications that lecturers gave for online lectures but I found it difficult to use" (R.10) As a response to statements above, if students had problem they got help from each other (ÖZTÜRK, 2021), in this interconnected with following statements:…”
Section: G Lack Of Technical Skillmentioning
confidence: 99%
“…"When there were courses that we worked in groups, I found it difficult to discuss with my group" (R.10). The students had difficulty, even could not do group work during COVID-19 pandemic (ÖZTÜRK, 2021). This was explained by the statement mentioned by respondents which reflected two main reasons, namely the limitation in online learning and student performance issues.…”
Section: Additional Difficulties: Difficult To Work In Groupmentioning
confidence: 99%
“…Teachers may submit instructional materials anytime and anywhere in this initial mode, which is helpful to them. Likewise, teachers or instructors typically exchange course resources (texts, videos, recordings, assignments, and so on) in their learning management systems (Öztürk, 2021;Rigo & Mikus, 2021). Students can download materials and upload assignments anytime as long as they can access the internet.…”
Section: Introductionmentioning
confidence: 99%